NOVEL ENTRY INHIBITORS FOR VIRAL HEPATITIS D TREATMENT: BULEVIRTIDE - A. K., SHUKLA; S., MISRA (International Journal of Current Pharmaceutical Research, 2023)
Chronic hepatitis D virus infection is the most severe form of viral hepatitis. Hepatitis delta virus (HDV) is a faulty RNA virus that needs hepatitis B virus surface antigen (HBsAg) for the completion of its life cycle. Hepatitis B virus (HBV) receptor, sodium taurocholate cotransporting polypeptide (NTCP), is used by HDV to infect hepatocytes. The replication of the HDV genome, which is a circular single-stranded RNA and encodes for a single HDAg that occurs in two forms (S-HDAg and L-HDAg), is carried out by the host RNA polymerases. Antiviral therapy is urgently needed to protect patients from hepatocellular carcinoma or end-stage liver disease and poses an important public health issue in many countries. There is still a need for efficient pharmacological therapies for chronic hepatitis D (CHD). A good strategy to stop new infections is to stop virus from entering cells. A new virion entry inhibitor called bulevirtide is now a promising treatment for both infections because it prevents the virion from entering the hepatocyte through the hepatic sodium/taurocholate cotransporting polypeptide Before bulevirtide's conditional approval by the EMA (European Medicines Agency) in July 2020 for the treatment of chronic HDV infection in adult patients with compensated liver disease, therapy options were restricted to the off-label use of pegylated interferon alfa. (NTCP) receptor. We will outline the most recent discoveries about the HDV life cycle that have prompted the development of noveldrug bulevirtide.